The Role of “Opportunity to Learn” in the Geometry Curriculum: A Multilevel Comparison of Six Countries - Bokhove, Christian; Miyazaki, Mikio; Komatsu, Kotaro; Chino, Kimiho; Leung, Allen; Mok, Ida Ah Chee (Frontiers in Education, 2019)
In international comparisons for mathematics in PISA and TIMSS, Asia outperforms England considerably at secondary level. For geometry this difference is even greater. With a new maths curriculum having come into play in England in 2014, and hence the need to explore the impact of the curriculum on student achievement, this article focuses on how differences in achievement might be attributed to differences in ‘opportunity to learn’ within a country’s curriculum. The aims of this paper are two-fold. Firstly we want to provide an integrated conceptual framework that combines elements from educational effectiveness, a curriculum model and ‘opportunity to learn’ for analysing curriculum effects, which we call the Dynamic Opportunities in the Curriculum (DOC) framework. Secondly, using multilevel models, we empirically investigate with TIMSS 2011 data whether the ‘opportunity to learn’ in the curriculum is associated with achievement in geometry education in six countries, thus validating that model. The results show that our conceptualisation of ‘opportunity to learn’ can be useful in analysing curriculum effects.